Avaliação da participação dos receptores TLR4 na nocicepção induzida por peptídeos da porção Spike da SARS-CoV2 em camundongos - Silva, Bruno Eduardo Gabriel Da (2024)
Coronavirus 2019 (COVID-19) is a highly transmissible infectious disease induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and resulted in serious problems in the health, economy, and development of countries around the world, leading, in extreme cases, to death of thousands of people. It is suggested that inflammation caused by the infection may play a relevant role in the development of pain during the virus' period of incubation. Several structures are involved in modulating this pain, for example, neurons and glial cells, which, when triggered, can increase the expression of receptors that activate intracellular pathways that culminate in the release of pro-inflammatory mediators. The Spike protein present on the surface of the S1 subunit of the virus is responsible for binding to the angiotensin-converting enzyme 2 (ACE 2) receptor and activating the transmembrane serine protease 2 (TMPRSS2), causing the viral RNA to enter the host cell. It also happens with other types of receptors, such as Toll-like receptor 4 (TLR4), whose function is to recognize molecular patterns associated with damage and pathogens (DAMPS and PAMPS). Therefore, the present study investigated the participation in nociception induced by peptides (PSPD2001, PSPD2002, and PSPD2003) present in the spike protein of SARS-CoV-2. The peptides were synthesized and donated in collaboration with the Department of Pharmacology at the University of São Paulo's Institute of Biomedical Sciences. Thus, we used male C57BL/6 and C57BL/6 TLR4(-/-) mice weighing between 20 and 25g. We applied the von Frey filament apparatus to assess the nociceptive threshold. For the induction of nociception, the peptides were administered intrathecally (i.t), and we evaluated the nociceptive threshold 1 hr, 3 hr, 5 hr, 7 hr, and 24 hr after injection. The involvement of TLR4 was investigated using the antagonist LPS-RS administered intrathecally (i.t). We used the inhibitor minocycline to evaluate the participation of microglia, and it was also administered intrathecally. The Western Blott assay was used to estimate the protein levels of TLR4, and the ELISA assay to evaluate the levels of TNF-α and IL-1β. The results indicate the participation of TLR4 and microglia in reducing the nociceptive threshold. Blocking the TLR4 receptor and inhibiting microglia led to the reversal of nociception. The results suggest that Spike protein peptides activated the TLR4 receptor, increasing the levels of pro-inflammatory cytokines and contributing to the development of pain.